EFFECT OF DIFFERENT NPK LEVELS AND BIOFERTILIZERS ON GROWTH AND FLOWERING CHARACTERS OF CHRYSANTHEMUM (Chrysanthemum morifolium Ramat.) - DARSHANKUMAR A. DARJI,; KIRAN KUMARI,; M. V. PATEL, (The Bioscan, 2021)
An experiment was carried out during 2019-2020, to investigate the effect of different NPK levels and biofertilizers on vegetative and flowering characters of chrysanthemum (Chrysanthemum morifolium Ramat.) variety ‘White Star’. The treatments comprised of combinations of three levels of recommended dose of NPK (100% RDF, 80% RDF and 60% RDF) and four biofertilizers (Azotobacter, PSB, KMB and NPK consortia). Among the treatments, maximum plant height at 30, 60 & 90 days after transplanting and at full bloom stage (16.17 cm, 29.67 cm, 52.80 cm and 58.17 cm, respectively), number of primary branches (5.80), plant spread (72.72 cm), number of leaves per plant (84.23) and number of suckers (5.99) were recorded in treatment T 6 (80% RDF + NPK consortia). Flowering characters were also significantly influenced by the treatments and earliest bud initiation (76.00 days), colour break stage (94.88 days), 50% flowering (109.80 days) and full bloom stage (115.30 days) was recorded in T 6 . Number of flowers per plant (10.40), flower diameter (12.68 cm), cut stem length (44.08 cm) and vase life of flowers (14.18 days) was recorded maximum in the same treatment.